Sylvester and the magic pebble - Steig, William, 1907-2003. (New York : Windmill, 1969)
In a moment of fright Sylvester the donkey asks his magic pebble to turn him into a rock but then can not hold the pebble to wish himself back to normal again.
Booklist.
Caldecott Medal/Honor.
Library Journal.
Booklist, March 1998.
Bulletin (Center for Children's books), November 2005.
Horn Book, September 2001.
Keywords: Caldecott medal books; Donkeys -- Fiction; Caldecott Medal; Donkeys -- Fiction